Tattered Stars - Cowles, Catherine (Toronto: The PageSmith LLC, 2021)
Be brave. Just for sixty seconds. Twenty breaths. One night changed them both forever. Their lives shattered, beyond repair, with jagged edges and pieces askew. Now, Everly has a chance to make things right. To bring healing to the place where everything fell apart. But it means facing the family her father almost destroyed, and the boy with the dark eyes--now grown--who still haunts her dreams. Just one breath away from having your life ripped out from under you. The last thing Hayes wants is another reminder of all the ways he failed sixteen years ago. When Everly drives back into Wolf Gap, his only mission is to get her to leave. For his family's sake, and for his own, those demons need to stay buried for good. But everything about this woman is a surprise, from her spine of steel to the sanctuary she hopes to create with the land her mother left behind. And Hayes is powerless to stay away. As a careful friendship sparks into something more, someone watches. And they'll do anything to tear it all apart .. Provided by the publisher.
Keywords: Friendship -- Fiction; Interpersonal Relationships -- Fiction; Man-Woman Relationships -- Fiction; Protected Areas -- Fiction; Romance